Use of Autologous Stem Cells for the Regeneration of Periodontal Defects in Animal Studies: a Systematic Review and Meta-Analysis - Algimantas Gaubys; Valdas Papeckys; Mindaugas Pranskunas (Stilus Optimus, 2018)
Objectives: To overview preclinical animal trials and quantify the effect size that stem cell therapy has on the regeneration of periodontal tissue complex. Material and Methods: A systematic MEDLINE (PubMed) online library search was conducted for preclinical animal studies in vivo, using autologous periodontal ligament, dental pulp, cementum, alveolar periosteal, gingival margin or adipose stem cell types for periodontal tissue complex regeneration purposes. Studies had to be published between 2007.09.01 and 2017.09.01 in the English language. Results: Online library search yielded 2099 results. After the title, abstract and full-text screening ten studies fit inclusion criteria and were pooled into meta-analysis. Overall the stem cell regenerative therapy had a statistically significant positive influence on the periodontal tissue regeneration when compared to the control groups. The biggest influence was made to the regeneration of cementum (standardised mean difference [SMD] 2.25 [95% confidence interval (CI) = 1.31 to 3.2]) while the smallest influence was made to the alveolar bone (SMD 1.47 [95% CI = 0.7 to 2.25]) the effect size for periodontal ligament regeneration was (SMD 1.8 [95% CI = 1 to 2.59]). Subgroup analysis showed statistically significant (P < 0.05) differences between different cell types in the alveolar bone and cementum regeneration groups and in alveolar bone group in relation to scaffold materials. Conclusions: Stem cell therapy has a positive impact on periodontal tissue complex regeneration. Such therapy has the biggest influence on cementum regeneration meanwhile alveolar bone regeneration is influenced by the least amount. However more and less diverse preclinical studies are needed to have a greater statistical power in future meta-analyses.